2003
DOI: 10.2214/ajr.181.3.1810831
|View full text |Cite
|
Sign up to set email alerts
|

Significance of and Contributing Factors for a High Resistive Index on Doppler Sonography of the Hepatic Artery Immediately After Surgery: Prognostic Implications for Liver Transplant Recipients

Abstract: High-resistance flow at the hepatic artery detected on Doppler sonography during the period immediately after transplantation is a frequent finding and is related to older donor age and prolonged period of ischemia. This finding has neither significant clinical repercussions nor prognosis implications for early and long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 27 publications
2
47
0
2
Order By: Relevance
“…High HARI has not been associated with worsening of clinical course or graft function; it may be related to older donor age and prolonged cold ischaemia. 15 Furthermore, this present study also found that a high HARI was more frequent during the early postoperative period. This was probably a result of the hepatic buffer response.…”
Section: Discussionsupporting
confidence: 79%
“…High HARI has not been associated with worsening of clinical course or graft function; it may be related to older donor age and prolonged cold ischaemia. 15 Furthermore, this present study also found that a high HARI was more frequent during the early postoperative period. This was probably a result of the hepatic buffer response.…”
Section: Discussionsupporting
confidence: 79%
“…The clinical insignificance of this high resistance flow had also been demonstrated in several reports. 4,[18][19][20] Our results agree with the HA buffer response theory in which the HA shows compensatory vasoconstriction reducing the arterial blood flow in response to portal hyperperfusion, thus leading to a high RI. 21,22 This phenomenon had been demonstrated intraoperatively by temporary clamping of the PV, which resulted in improved HA flow.…”
Section: Omar Abdelaziz Et Al/experimental and Clinical Transplantatisupporting
confidence: 88%
“…19 Other theories have related the early and transient elevation of the HA RI after DDLT to the older donor grafts, prolonged period of cold ischemia and preservation injury, graft steatosis, and chronic cholestatic disease as an indication for trans plant. 18,20,23 In addition, a decreased HA RI (< 0.50) can also be observed in the early postoperative period, although it was less common than a high HA RI. These low HA RI values might be caused by surgical edema, with low HA RI values ordinarily returning to a normal level within 6 months.…”
Section: Omar Abdelaziz Et Al/experimental and Clinical Transplantatimentioning
confidence: 99%
“…As a result, complete occlusion of the hepatic artery results in infarction or necrosis of the liver parenchyma and may lead to fulminant hepatic failure in the early post-transplantation period. Doppler US allows correct identification of hepatic artery thrombosis in up to 90% of cases (Crossin et al, 2003;Garcı´a-Criado et al, 2003;Glockner & Forauer 1999;Nghiem et al, 1996). At doppler US examination, there is usually complete absence of both proper hepatic and intrahepatic arterial flow (Chong, 2004;Kok T et al, 1998;Nghiem et al, 1996).…”
Section: Hepatic Artery Thrombosismentioning
confidence: 99%
“…MR venography can provide an excellent visualization of portal vein thrombosis and can facilitate the differentiation of thrombosis from slow flow (StaffordJohnson et al, 1998;Unsinn et al, 2003). At contrast material-enhanced CT, portal vein thrombosis is seen as a low-attenuation filling defect (Ametani et al, 2001;Garcı´a-Criado et al, 2003;Unsinn et al, 2003). Portal vein stenosis with thrombus formation in the immediate postoperative period is quickly diagnosed with Doppler US and is managed surgically.…”
Section: Portal Vein Thrombosismentioning
confidence: 99%